Revisiting the NH3-SCR performance of MnO2 with different crystal phases: From electronic structure to catalytic activity - Yue, Yi; Xiong, Shangchao; Ou, Hongjun; Yang, Yi; Sun, Xiaoyu; Wang, Houlin; Xi, Yingwei; Gong, Zhengjun; Chen, Jianjun; Li, Junhua (Applied catalysis. B, Environmental, 2026)
Manganese oxides are among the most promising low-temperature NH3-selective catalytic reduction (NH3-SCR) catalysts. MnO2 with different crystal phases (α-, β-, γ-, and δ-MnO2) exhibits significantly different NH3-SCR performance. The fundamental factors influencing the activity of MnO2 with different crystal phases remain a subject of considerable debate. This study finds that β- and δ-MnO2 show poor activity due to low reactivity and poor NH3 adsorption. In contrast, α- and γ-MnO2 show high activity but differ in optimal reaction temperature windows. The smaller Mn-O coordination number and longer Mn-O bond distance in α-MnO2 result in an upward shift of its d-band center. Therefore, α-MnO2 exhibits stronger coupling between the Mn-d and N-p orbitals during NH3 adsorption, promoting *NH3 activation. As a result, α-MnO2 outperforms γ-MnO2 in low-temperature catalytic activity. This study reveals the impact of microscopic electronic orbital coupling on macroscopic catalytic performance, providing new insights for developing advanced low-temperature NH3-SCR catalysts. [Display omitted] •Coordination environments cause SCR performance differences in MnO2 crystal phases.•d-Band shifts lead to varied NH3 activation barriers in α- and γ-MnO2.•Poor redox ability at low temperature makes β-MnO2 catalytically less active.•Nitrate buildup on δ-MnO2 inhibits SCR performance.